Association of breed and non-genetic factors with freezing point and milk attributes of Zebu cattle - Navav Singh, Sanjita Sharma, Vishnu Sharma, Sita Ram Gupta, Govind Singh Dhakad and Satendra Kumar Yadav (Indian Journal of Dairy Science, 2022)
The present experiment was conducted to study the milk quality of indigenous cattle which are important for farmers, manufactures and consumers. For this study, we have collected 150 milk samples of three different indigenous cattle breeds viz. Kankrej, Sahiwal, and Rathi from semi-arid region of Rajasthan, India. The samples were evaluated for the milk fat, protein, lactose, solid not fat (SNF), somatic cell count (SCC), pH, electric conductivity and freezing point, and observed the relationship of breed, stage of lactation, parity and body condition score (BCS) with their milk constituents and freezing point. Total Protein, freezing point and electric conductivity of milk differed significantly (P